The research agenda for improving health policy, systems performance, and service delivery for tuberculosis control: a WHO perspective - Nunn Paul; Harries Anthony; Godfrey-Faussett Peter; Gupta Raj; Maher Dermot; Raviglione Mario (Bulletin of the World Health Organization, 2002)
The development of WHO's DOTS strategy for the control of tuberculosis (TB) in 1995 led to the expansion, adaptation and improvement of operational research in this area. From being a patchwork of small-scale studies concerned with aspects of service delivery, TB operational research shifted to larger-scale, often multicountry projects that were also concerned with health policy and the needs of health systems. The results are now being put into practice by national TB control programmes. In 1998 an ad hoc committee identified the chief factors inhibiting the expansion of DOTS: lack of political will and commitment, poor financial support for TB control, poor organization and management of health services, inadequate human resources, irregular drug supplies, the HIV epidemic, and the rise of multidrug resistance. An analysis of current operational research on TB is presented on the basis of these constraints, and examples of successful projects are outlined in the article. We discuss the prerequisites for success, the shortcomings of this WHO- supported programme, and future challenges and needs.